Ontogeny of pancreatic exocrine function. - Kolacek, S (1990)
Exocrine pancreatic proteolytic activity, determined by serial measurement of faecal chymotrypsin concentration, was investigated in 21 preterm infants (23-32 weeks' gestation) during the first 28 days of life. The overall chymotrypsin concentration range was similar to that already described in term infants showing that pancreatic chymotrypsin secretion is equally well developed at birth in the preterm infant. A chymotrypsin concentration peak, seen in term infants at 4 days, did not occur in this study until day 8, suggesting a slower initiation of pancreatic exocrine function in the preterm infant. Median faecal chymotrypsin concentrations, calculated for each baby using data from stools passed between day 2 and day 12 of life, were significantly lower in infants who were small for gestational age when compared with those who were an appropriate size for gestational age. The lower chymotrypsin concentration in infants who were small for gestational age suggests a deleterious effect of intrauterine growth retardation on pancreatic exocrine function which may be a factor in limiting postnatal catch up growth.